Decentralised onfarm seed potato production from prebasic minitubers: a case study from Nepal - Schulz, S.; Wells, G.J.; Baniya, Bimal K.; Barakoti, T.P.; Kharel, G.; Saha, B.; Thapa, B.V.; Ojha, D.N. (Cambridge University Press, 1998)
The on-farm performance of more than 150 000 pre-basic potato (Solanum tuberosum) minitubers of 1–10 g was monitored over two years in contrasting environments in Nepal. Average minituber productivity (grams of basic seed produced per minituber planted) was 171 g in the southern plains and 116 g in the hills. Although the performance of minitubers varied between environments, minituber sizes and potato varieties, the overall results clearly indicated that minitubers can be successfully multiplied by small-scale farmers. This technology therefore allows for the highly decentralized production of basic seed which, in turn, will reduce farmers' dependence on an unreliable and costly supply of bulky conventional seed.